2016
DOI: 10.1136/bmjopen-2015-010809
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based self-management support for adults with asthma: a qualitative study among patients, general practitioners and practice nurses on barriers to implementation

Abstract: ObjectivesThe aim of this study was to explore barriers among patients, general practitioners (GPs) and practice nurses to implement internet-based self-management support as provided by PatientCoach for asthma in primary care.SettingPrimary care within South Holland, the Netherlands.ParticipantsTwenty-two patients (12 women, mean age 38 years), 21 GPs (6 women, mean age 52 years) and 13 practice nurses (all women, mean age 41 years).DesignA qualitative study using focus groups and interviews.OutcomesBarriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…The review showed that human factors approaches are nearly always adopted to some extent in the design, development and evaluation of mobile applications. Moreover, an effective implementation strategy for Internet-based self-management support in asthma care should focus on human factor barriers [27]. Overall, clinicians view asthma mHealth technology as supporting the aims of the patient-centred medical home.…”
Section: Human Factors Applied To the Design Development And Evaluatmentioning
confidence: 99%
“…The review showed that human factors approaches are nearly always adopted to some extent in the design, development and evaluation of mobile applications. Moreover, an effective implementation strategy for Internet-based self-management support in asthma care should focus on human factor barriers [27]. Overall, clinicians view asthma mHealth technology as supporting the aims of the patient-centred medical home.…”
Section: Human Factors Applied To the Design Development And Evaluatmentioning
confidence: 99%
“…These arguments bring up another important point -much attention in mHealth intervention research is placed on the barriers of acceptance and hypothetical facilitators [28][29][30], and less on practical solutions to not only use PGD but moreover to consider services that could support the use of PGD and mHealth.…”
Section: Discussionmentioning
confidence: 99%
“…These arguments bring up another important point -much attention in mHealth intervention research is placed on the barriers of acceptance and hypothetical facilitators [23][24][25], and less on practical solutions to not only use PGD but moreover to consider services that could support the use of PGD and mHealth.…”
Section: Discussionmentioning
confidence: 99%